Analisis Kemampuan Penalaran dan Pemecahan Masalah Matematika pada Siswa Bimbel SIBABA - Yulfani, Siswi; Putra, Lisa Virdinarti; Akadiyaningsih, Dwi; Wibisono, Bagas; Nurohmah, Siti (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
The purpose of this study was to analyze the ability to think mathematically and solve problems of students who are members of the SIBABA Bimbel. The research methodology used in this research is descriptive qualitative. Participants in this study were fifth grade elementary school students who were members of SIBABA Bimbel. Data is collected through observation, documentation and relevant references. Students are given tests that assess their reasoning abilities, problem-solving skills, and understanding of mathematics. Data analysis used is descriptive analysis. The results showed that students had difficulty in reasoning because they did not fully understand the concept of reasoning itself. This causes difficulties for students in solving problems, finding solutions, and answering questions. However, students were able to solve problems well and achieve all the maximum indicators, demonstrating their understanding of the form and meaning of problems and how to solve them. Therefore, further guidance in the aspect of reasoning is very important for student progress.